The impact of artificial intelligence in the digital society / Dr Zuhairah Hasan ... [et al.] - Hasan, Zuhairah (Office of the Deputy Vice-Chancellor (Research & Innovation), 2023)
Artificial intelligence (“AI”) is the simulation of human intelligence processes by machines that can perform and think like human beings. The goals of artificial intelligence include computer-enhanced learning, reasoning, and perception. AI is being used today across different industries from medical, business and healthcare industries as AI gives computers or machines the capacity to learn, reason and apply logic. With the introduction of AI the “Transformation Nasional 2050”, Malaysia has proven its preparedness to embrace the diffusion of advanced technological developments. The transformative impact of AI on our society in many aspects such as economic, legal, and regulatory implications need to be discussed and addressed. Thus, this article will highlight some insights on the impacts of AI in the society. Correspondingly, this article also will highlight several ethical issues concerning AI.